Impact of most promising Ebola therapies on survival: a secondary analysis during the tenth outbreak in the Democratic Republic of Congo - Esther Mamu Kikwango; Pierre Z. Akilimali; Nguyen Toan Tran (Virology Journal)
Abstract Background MAb114, REGN-EB3, Remdesivir, and ZMapp, which are monoclonal antibody-based treatments, have been compared and shown to be promising therapies against the Ebola Virus Disease (EVD). There has been no comparison between these medications and standard treatment (without antiviral). Our study aimed to examine the contribution of each regimen compared to standard treatment on the survival of EVD patients and assess whether this association was modified by EVD vaccination (rVSV-ZEBOV Ebola vaccine) status. Methodology: We performed a secondary analysis study using retrospective cohort data obtained from four EVD treatment centers located in Katwa, Mangina, Butembo, and Beni in the North Kivu region. The main outcome measure was mortality within a 28-day period among 781 included patients. A Cox model was used to identify predictors of survival in hospitalized EVD patients. Results: Vaccinated EVD patients were 1.7 times less likely to die compared to unvaccinated patients (3.70 days vs. 5.00 days; p = 0.0002). Delaying care and treatment at EVD treatment centres increased mortality risk by 5% for each day following symptom onset. Compared to the standard treatment group, adjusted mortality rates were significantly reduced in the groups receiving MAb114 (0.27, p < 0.001), REGN-EB3 (0.26, p < 0.001), and Remdesivir (0.38, p = 0.005). ZMapp also showed a reduction, though with borderline statistical significance (0.47, p = 0.032). Conclusions: Prompt identification and treatment, along with enhanced supportive care (such as replenishing fluids and electrolytes and managing symptoms), significantly improve survival chances. Concurrently, administering vaccines and using mAb114, REGN-EB3, and, to some extent, Remdesivir further increase patient survival rates.